2017
DOI: 10.15420/cfr.2016:15:2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Heart Failure Care Planning: Considerations in Older Patients

Abstract: In developed countries, it is estimated that 1-2 % of the adult population has heart failure (HF), with the prevalence increasing to more than 10 % in those aged >70 years.1 Despite advances in therapies for heart failure with reduced ejection fraction (HFrEF), it remains a condition associated with significant morbidity and mortality, punctuated by episodes of unplanned hospitalisation. 2HF is one of the commonest causes of unscheduled hospital admissions 3 and data consistently show a lower uptake of evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…25 The recognition of frailty is the first step for an accurate risk stratification and planning a tailored therapeutic plan. 26,27 However, several knowledge gaps exist. First, a unique definition of this syndrome in patients with HF is still lacking.…”
Section: Assessment and Management Of Frailty In Hfmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The recognition of frailty is the first step for an accurate risk stratification and planning a tailored therapeutic plan. 26,27 However, several knowledge gaps exist. First, a unique definition of this syndrome in patients with HF is still lacking.…”
Section: Assessment and Management Of Frailty In Hfmentioning
confidence: 99%
“…Several measurements have been proposed to assess frailty, and a huge variety of methods and instruments are available. 11,28,29 The most widely used tools to assess frailty are Fried's phenotypic definition of frailty and the frailty index, described in detail elsewhere. 3,11,30 There are also self-report questionnaires or instruments based on the assessment of single performances (i.e.…”
Section: Assessment and Management Of Frailty In Hfmentioning
confidence: 99%
“…Indeed, while in OPTIMIZE-HF [22] patients over 65 years old, the BNP plasma value adequately predicted 1-year mortality and hospital readmission, the meta-analysis of Troughton et al, [30] clearly demonstrated how the survival benefit of a BNP-guided therapy post-discharge seemed to be effective only in younger (<75 years old) HF patients. Elderly HF patients more frequently experience comorbidity, frailty, multiple therapies, and significant cognitive impairment that have a notable impact on outcomes [31] independent of levels of biomarkers. In a recent review on plasma biomarkers, Correale et al [32] stressed the fact that the role of biomarkers in elderly HF patients has been influenced by the presence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition many confounding comorbidities make treatment more difficult; these include iron deficiency, 33 muscle wasting, 20 , 21 and frailty, many making drug side effects 18 more likely. Although we are beginning to address the specific problems of drug therapy in the elderly, much remains left to do to improve the quality and appropriateness of our care in this vulnerable group 34 such as by planning specific care plans for older or frail HF patients 35 …”
Section: Drug Therapy In the Older Or Frail Hf Patientmentioning
confidence: 99%